2018
DOI: 10.3390/nu10111632
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Psychophysical Dose-Response Behaviour across 16 Sweeteners

Abstract: Reduction or replacement of sucrose while maintaining sweetness in foods is challenging, but today there are many sweeteners with diverse physical and caloric compositions to choose from. The choice of sweetener can be adapted to match reformulation goals whether these are to reduce calories, lower the glycaemic response, provide bulk or meet criteria as a natural ingredient. The current study sought to describe and compare the sweetness intensity dose-response, sweetness growth rate, sweetness potency, and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 48 publications
(98 reference statements)
2
34
0
Order By: Relevance
“…Thus, the relatively low effect of sucrose on sweet taste intensity in the apple nectar matrix could be because the dose-response curve was flattening at higher concentrations. Indeed, recent studies have shown that sucrose as well as most alternative sweeteners, both nutritive and non-nutritive ones, follow sigmoidal dose-response functions [53,54]. However, in both cases, the essentially linear part of the curve for sucrose was roughly around 6-18% w/v [53,54].…”
Section: The Effects Of Matrix On Sweetness-aroma-pectin Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the relatively low effect of sucrose on sweet taste intensity in the apple nectar matrix could be because the dose-response curve was flattening at higher concentrations. Indeed, recent studies have shown that sucrose as well as most alternative sweeteners, both nutritive and non-nutritive ones, follow sigmoidal dose-response functions [53,54]. However, in both cases, the essentially linear part of the curve for sucrose was roughly around 6-18% w/v [53,54].…”
Section: The Effects Of Matrix On Sweetness-aroma-pectin Interactionsmentioning
confidence: 99%
“…Indeed, recent studies have shown that sucrose as well as most alternative sweeteners, both nutritive and non-nutritive ones, follow sigmoidal dose-response functions [53,54]. However, in both cases, the essentially linear part of the curve for sucrose was roughly around 6-18% w/v [53,54]. With 9.8% w/v sugar present in the base product and 2.5-7.5% w/w sucrose added, the total amount of sugar in the samples is not likely to have exceeded the amount of 18% w/v sugar, thereby entering the non-linear flattening part of the curve.…”
Section: The Effects Of Matrix On Sweetness-aroma-pectin Interactionsmentioning
confidence: 99%
“…The availability of low‐ or no‐calorie sweeteners means it is possible to formulate foods and beverages that retain their sweetness at a substantially reduced sugar content. There are currently many commercially available sweeteners capable of matching the perceived sweetness intensity of sucrose (O'Brien‐Nabors, ; Wee, Tan, & Forde, ), although they vary considerably in their sweetness quality, intensity, temporal properties, and presence of side tastes (Fujimaru, Park, & Lim, ; Ketelsen, Keay, & Wiet, ; Reyes, Castura, & Hayes, ). These differences are often further amplified in food matrices with complex taste profiles, which studies comparing sweeteners in water may not accurately reflect (Fujimaru et al., ; Reyes et al., ; Zhao & Tepper, ).…”
Section: Introductionmentioning
confidence: 99%
“…The availability of low-or nocalorie sweeteners means it is possible to formulate foods and beverages that retain their sweetness at a substantially reduced sugar content. There are currently many commercially available sweeteners capable of matching the perceived sweetness intensity of sucrose (O'Brien-Nabors, 2016;Wee, Tan, & Forde, 2018), although they vary considerably in their sweetness quality, intensity, temporal properties, and presence of side tastes (Fujimaru, Park, & Lim, 2012;Ketelsen, Keay, & Wiet, 1993;Reyes, Castura, & JFDS-2019-1046Submitted 7/1/2019, Accepted 11/22/2019 Forde are from Clinical Nutrition Research Center, A * STAR Singapore Inst. for Clinical Sciences, Medical Drive, Singapore.…”
Section: Introductionmentioning
confidence: 99%
“…D-Allulose (D-ribo-2-hexulose), a C-3 epimer of D-fructose, is one of the rare sugars that are present in limited quantity in nature. D-Allulose has 70% of sweetness relative to sucrose, and when allulose and sucrose were blended in a 1:1 mixture, this blend achieved a near identical dose-response curve to sucrose (Wee et al, 2018). In humans, approximately 70% of the ingested D-allulose is absorbed in the small intestine and excreted into the urine without being further metabolized (Iida et al, 2010).…”
Section: Introductionmentioning
confidence: 99%